1999
DOI: 10.1177/107110079902000205
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Lateral Ankle Ligaments Using a Split Peroneus Brevis Tendon Graft

Abstract: Thirty-one consecutive ankles in 30 patients with chronic lateral ankle instability were reconstructed using a split peroneus brevis tendon graft. All patients had pain and instability despite adequate treatment and a rehabilitation program. Six patients had clinical and radiographic evidence of associated subtalar laxity. Four patients (four ankles) had prior Brostrom ligament reconstructions. The average time from the initial injury or treatment to surgery was 23 months. At a mean follow-up of 44 months (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 20 publications
0
67
1
Order By: Relevance
“…Colville et al found that 12 of 15 patients available at 3.5 years follow-up showed radiographically confi rmed restoration of mechanical stability [ 106 ]. Sammarco et al reported good-to-excellent results in 29 of 31 ankles (94 %) at a mean follow-up of 44 months using a split peroneus brevis tendon graft for reconstruction [ 107 ].…”
Section: Lateral Ligament Instabilitymentioning
confidence: 97%
“…Colville et al found that 12 of 15 patients available at 3.5 years follow-up showed radiographically confi rmed restoration of mechanical stability [ 106 ]. Sammarco et al reported good-to-excellent results in 29 of 31 ankles (94 %) at a mean follow-up of 44 months using a split peroneus brevis tendon graft for reconstruction [ 107 ].…”
Section: Lateral Ligament Instabilitymentioning
confidence: 97%
“…Many different tendon grafts have been used historically; most recently, the gracilis tendon has gained popularity due to its size, ease of harvest, and the minimal long-term disability associated with the harvest. 1,[18][19][20][21][48][49][50][51][52][53][54] Use of an anatomic reconstruction has replaced the historical tenodesis procedures such as the Evans, Watson-Jones, Chrisman-Snook, and others that have been shown anatomically and in long-term clinical studies to limit subtalar motion. 8,16,17,22,[55][56][57][58][59][60][61][62][63] In the authors' experience, mistakes in harvesting involve difficulty in isolating the tendon (approach) and amputating the tendon short.…”
Section: Surgical Technique Brostrom Proceduresmentioning
confidence: 99%
“…Surgery is indicated when non‐operative treatment has failed. There has been a general trend away from the non‐anatomical procedures, on account of their increased risk of complications and adverse effects on the biomechanics of the ankle and hindfoot, in favour of the ‘anatomic’ procedures . The modified Brostrom‐Gould (MBG) is commonly regarded as the treatment of choice, owing to its relative simplicity and safety .…”
Section: Introductionmentioning
confidence: 99%